Modelling terrestrial route networks to understand inter-polity interactions (southern Etruria, 950-500 BC). (May 2019) - Prignano, Luce; Morer, Ignacio; Fulminante, Francesca; Lozano, Sergi
Abstract: Ancient regional routes were vital for interactions between settlements and deeply influenced the development of past societies and their "complexification". At the same time, since any transportation infrastructure needs some level of inter-settlement cooperation to be established, they can also be regarded as an epiphenomenon of social interactions at the regional scale. Here, we propose to analyze ancient pathway networks to understand the organization of cities and villages located in a certain territory, attempting to clarify whether such organization existed and if so, how it functioned. To address such a question, we chose a quantitative approach. Adopting network science as a general framework, by means of formal models, we try to identify how the collective effort that produced the terrestrial infrastructure was directed and organized. We selected a paradigmatic case study: Iron Age southern Etruria, a very well-studied context, with detailed archaeological information about settlement patterns and an established tradition of studies on terrestrial transportation routes, perfectly suitable for testing new techniques. The results of the modelling suggest that a balanced coordinated decision-making process was shaping the route network in Etruria, a scenario which correlates well with the picture elaborated by different scholars using a more traditional technique.